Crosstalk Between Skeletal Muscle and Immune System: Which Roles Do IL-6 and Glutamine Play? - Rogeri, Patricia S.; Gasparini, Sandro O.; Martins, Gabriel L.; Costa, L. K. F.; Araujo, Caue C.; Lugaresi, Rebeca; Kopfler, Mariana; Lancha, Antonio H. (Frontiers in Physiology, 2020)
The skeletal muscle was always seen from biomechanical and biochemical views. It is well-established that an active muscle brings many benefits for different body organs and tissues, including the immune system. Since the 1970s, many studies have shown the importance of regular exercise and physical activity in increasing the body’s ability to fight opportunist infections, as well as a strategy to fight established diseases. This interaction was mainly attributed to the glutamine, a non-essential amino acid produced by the active skeletal muscle and primarily consumed by rapidly dividing cells, including lymphocytes and monocytes/macrophages, as their main source of energy. Therefore, these cells’ function would be significantly improved by the presence of a bigger glutamine pool, facilitating phagocytosis, antigen-presentation, proliferative capacity, cytokine synthesis and release, among other functions. Despite its importance, glutamine is not the only molecule to connect these two tissues. The presence of cytokines is crucial for a proper immune system function. Many of them have well-established pro-inflammatory properties, while others are known for their anti-inflammatory role. Interleukin-6 (IL-6) however, has been in the center of many scientific discussions since it can act as pro- and anti-inflammatory cytokine depending on the tissue that releases it. Skeletal muscle is an essential source of IL-6 with anti-inflammatory properties, regulating the function of the immune cells after tissue injury and the healing process. Therefore, this review aims to discuss further the role of these four components (glutamine, and interleukin-6, and its interface with monocytes/macrophages, and lymphocytes) on the communication between the skeletal muscle and the immune system.